EXPERIMENTAL STUDY OF NATURAL FLOW FLAT PLATE SOLAR WATER HEATER IN BASRA CITY - Hussien S. Sultan; Ammar A. Ojimi; Amani J. Majeed; Safaa Faisal (Proceedings on Engineering Sciences)
Using solar energy for heating, cooking, desalination, electric generation and other human community requirements represents the best solution for two important world challenges, which are fossil fuel resources depletion and pollution. In this study, an experimental study for heating water by solar energy is performed at Basra city climate in Iraq. The city is located at Longitude: 47.78o and Latitude: 30.508o. The natural flow flat plate heater is directed towards the south with an angle of 30o with the horizontal. Tests for the solar water heater are implemented for five consecutive days from the month of July during the year 2021. For the present solar water heater, maximum temperature of the stored water was 48 0C, while the maximum measured temperature of the water leaving the collector is 85.9 0C The total pressure drop was calculated and it is found that the pressure drop in the collector constitutes approximately 25 % of the total pressure that causes the circulation. The maximum natural flow hot water rate is predicted to be 14*10 -4 kg/s. The maximum efficiency of the solar heater is expected to be 60 %.